Student Study Habits Challenges and Academic Performance in All Subjects’ Area of the Grade 6 Learners of Manicahan Central School - Gutierrez, Isiah Gimel R.; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the challenges faced by Grade 6 learners in developing effective study habits, focusing on the influence of personal factors, home environment and technology and internet use. Data was gathered through a Likert scale survey administered to 55 students, exploring their study habits, academic performance, and the challenges they encounter in maintaining effective study routines. The study found that personal factors such as time management, motivation, and self-discipline were significant barriers to effective studying. The home environment, characterized by distractions, lack of a proper study space, and limited family support, further hindered students' study efforts. Additionally, the excessive use of gadgets and social media led to reduced focus on academic tasks. The findings suggest that improving students' study habits requires addressing both internal and external factors. Recommendations include providing students with time management and self-discipline training, improving the home study environment, adjusting school workloads, offering more personalized teacher support, and promoting responsible technology use. By implementing these strategies, students can develop more effective study habits, leading to improved academic performance.